การผลิตเชื้อเพลิงชีวภาพสำหรับอากาศยานจากน้ำมันปาล์มผ่านไฮโดรดีออกซิจิเนชันและไฮโดรไอโซเมอไรเซชัน - พชร ฉินทกานันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
According to the increasing demand for air transport with growing awareness of environmental issues caused by fossil fuels burning, every country attemps to produce bio-jet fuel for replacing the fossil fuel. However, bio-jet fuel produced from palm olein or animal fat is usually suffered from poor cold flow properties due to its high freezing point. Hence, the objective of this research is to study and develop the production process of bio-jet fuel derived from palm oil using zeolites-based catalysts. This research aimed to produced bio-jet fuel with high content of iso-alkanes to reduce the freezing point of fuel via hydroisomerization (HI) of normal-alkanes along with hydrodeoxygenation (HDO) and hydrogenation (HG) to eliminate oxygenated compounds and unsaturated compounds. In this research, the effects of 10 wt% nickel (Ni) based on the weight of catalyst and loaded on four types of zeolite support (NH₄-Beta, H-Beta, ZSM-5 and Y) on the catalytic efficiency were investigated. The Ni-based zeolite catalysts were prepared by incipientwetness impregnation method. The used of Pt-Ni bimetallic catalysts with Pt/(Pt+Ni) wt ratio between 0.05- 0.15 at a net metal content of 10 wt% were also studied. Catalyst activity was tested in a batch reactor and the effect of various reaction parameters such as initial H₂ pressure (25-40 bar), reaction temperature (300-380 °C) reaction time (2-8 h) and catalyst concentration (2.8-17.0 wt% of palm oil) on the product selectivity and yield were investigated. Before the reaction, the catalyst was in-situ reduced at 400 °C for 2 h under 10 bar of H₂ pressure. From the results, bio-jet fuel with the highest iso-/n-alkanes ratio of 1.67 with low content of oxygenated and unsaturated compounds was obtained with 10%Ni/NH₄-Beta when the concentration of catalyst at 5.7 wt% based on palm oil was applied under 40 bar initial H₂ pressure at 360 °C for 4 h to achieve the bio-jet fuel yield of 20.8 wt% based on fed palm oil. Since the obtained bio-jet fuel had high iso-alkanes content of 24.9% it could reduce the freezing point to -72 °C. In addition, it was found that the blending of liquid product having the freezing point of -28 °C with a commercial jet fuel (JETA-1) at 30 vol% yielded a blended bio-jet fuel with a freezing point of -53 °C, which was still in the requirement of the ASTM D7566 criteria.